The Effect of Cold Eddy on Acoustic Propagation (Case Study: Eddy in the Persian Gulf) - MAHPEYKAR, Omid; ASHTARI LARKI, Amir; AKBARI NASAB, Mohammad (Archives of Acoustics, 2022)
It is essential for oceanographers to study the effects of marine phenomena such as currents, surface mixed layer, eddies, internal waves, and other ocean features on acoustic propagation, as most marine measurement equipment operates on this basis, like sonar. The eddy impact on acoustic transmission in the marine environment is very significant because changes in temperature and salinity disrupt the sound speed due to the presence of eddy, thus the acoustic propagation in the sea. Although cold eddies are in the Persian Gulf widely, one eddy is selected to study their impacts on acoustic propagation because they have similar properties in terms of temperature and salinity. In this research, after identifying eddies in the Persian Gulf automatically, the effect of a cold eddy on acoustic propagation was investigated at different depths using the BELLHOP model. Most eddies are cyclonic with 5–10 km of radius based on algorithm outputs. Studies on the lifespan of eddies showed that the occurrence of cyclonic eddies with a lifespan of more than three days is more than anticyclonic ones. Examination of the eddy effect on acoustic propagation showed that the transmission loss (TL) during the progress of the acoustic wave across the eddy increases with increasing the depth of the sound source. Also, the presence of cold eddy compared to the conditions it does not exist increases the transmission loss. The study of three-dimensional acoustic propagation also confirmed the obtained results in two-dimensional mode and clearly showed the role of cold eddy in increasing the TL.